Influence of the Damping System on the Vehicle Vibrations - Svoboda, Martin; Schmid, Vaclav; Sapieta, Milan; Jelen, Karel; Lopot, Frantisek (Manufacturing Technology Journal, 2019)
The aim of the work was to evaluate the whole system of the springs of a passenger car. The influence of inflation and the type of tires on the acceleration of the various parts of the car (axle, steering wheel, driver's seat attachment, body shell and acceleration affecting the driver) was investigated. The types of shock absorbers and springs of the passenger car were also examined. The sensors used acceleration and pressure sensors between the wheel and the road using test stands. The benefits and reserves of the individual systems were compared, and in the systems with the cushioning rigidity, all the suspension setups were evaluated. The work was done experimentally in laboratory environment as well as in real operation.
Keywords: mechanical system; oscillation; experiment; vehicle